A kisajátítási kártalanítás - Andorkó, Imre (Debreceni Jogi Műhely, 2014)
The regulation of expropriation law is indicative of the sound of rule of law. It shows how the state treats vulnerable groups, and people adversely affected by expropriation. In this paper I will give a short overview of the rules concerning compensation for expropriation, from the inception of expropriation law, right up to 2014. I pay particular attention to the characteristics of the regulation in the socialist era between 1948, and the regime change in 1989/1990. I expand on how Hungary tried to free itself of the burdensome heritage of the socialist regulation of that law, after the regime change of 1989/1990. Then I review the current status of legal regulation concerning compensation for expropriation that gives me a great opportunity to and explain suggestions de lege ferenda.